Utilising Smartphone Light Sensors to Measure Egg White Ovalbumin Concentration in Eggs Collected from Yinchuan City, China - Linlin Liu; Hualin Bi (Journal of Chemistry)
Cost-effective, portable, and rapid smartphone sensors will play a critical role in bringing chemical detection technologies from central laboratories to simple laboratories, such as those of schools in less-developed area. In this work, we study whether eggs in Yinchuan have a higher concentration of ovalbumin than that in ordinary eggs. We summarise previous research on sensors built inside smartphones, as well as some developments in the current literature, and develop a simple experimental procedure that utilises the light sensor of a smartphone to analyse light intensity and thereby determine the ovalbumin content of egg white cheaply and quickly. Most of the materials required for conducting this experiment can be easily found in simple school laboratories, and it allows solution concentrations to be quickly assessed by high school students in the data collection and analysis phase. Indeed, the data collected using smartphone light sensors were similar to those obtained using a spectrometer. It was concluded that egg white ovalbumin concentration in eggs collected from Yinchuan is higher than that in ordinary eggs.